1994
DOI: 10.1200/jco.1994.12.7.1402
|View full text |Cite
|
Sign up to set email alerts
|

Prostate-specific antigen decline: a major prognostic factor for prostate cancer treated with radiation therapy.

Abstract: PSA values are of major prognostic significance in assessing the 4-year results of radical radiation therapy for localized prostate cancer. The rate of decline of PSA values is the strongest predictor of outcome and might help to identify a subset of patients with poorer prognosis who may benefit from early hormonal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…The interpretation of the PSA rate of decline following radiotherapy, as measured by the PSA slope, is more controversial. Some studies have shown a relationship between the magnitude of the PSA slope and clinical outcomes [35,37], while other studies have not [38-40]. Regardless, the rate of PSA decline is reflective of the cellular response to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the PSA rate of decline following radiotherapy, as measured by the PSA slope, is more controversial. Some studies have shown a relationship between the magnitude of the PSA slope and clinical outcomes [35,37], while other studies have not [38-40]. Regardless, the rate of PSA decline is reflective of the cellular response to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of the PSA rate of decline following radiotherapy, as measured by the PSA slope, is more controversial. Some studies have shown a relationship between the magnitude of the PSA slope and clinical outcomes [35,37], while other studies have not [38][39][40]. Regardless, the rate of PSA decline is reflective of the cellular response to radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Benign PSA bounces were common with 33.3% of all patients. The median time to PSA bounce was 13 months (range, [6][7][8][9][10][11][12][13][14][15][16][17][18]. The median height of PSA bounce was 0.34 ng/mL (range, 0.21-1.39).…”
Section: Resultsmentioning
confidence: 99%
“…While recent studies have demonstrated that a lower PSA nadir (<0.5 ng/ mL) has been associated with superior clinical disease-free survival (15,16) , the interpretation of the decline rate of PSA following radiotherapy is controversial. Some reports have shown a positive relationship between the increase of the decline rate and clinical outcome, while others have negative (11,(17)(18)(19)(20) . Shi et al (21) reported that a rapid PSA decline in the !irst year after external beam radiotherapy is positively associated with prostate cancer speci!ic mortality.…”
Section: Introductionmentioning
confidence: 99%